Estimating the potential of residential heat pumps to reduce surplus electricity using the flexible demand tool in EnergyPLAN - Campos, José; Munkácsy, Béla (International Journal of Sustainable Energy Planning and Management, 2025)
Energy system flexibility is necessary to accommodate the expansion of variable renewable electricity. The EnergyPLAN tool is useful for simulating energy systems with high shares of variable renewable energy sources by representing supply and demand side technologies and verifying the balance of the system with an hourly resolution. This paper proposes a methodology to investigate the potential and availability of the flexible electricity demand of residential (individual) heat pumps providing heating, cooling, and domestic hot water to reduce surplus (excess) generation. The methodology was applied to a theoretical scenario of the Hungarian electricity system as a case study. The theoretical flexible demand resulted in an average monthly reduction of 30% in surplus power. At its peak in February, the reduction reached nearly 50% of the surplus power. However, during the most critical period (May), it dropped to just 7% due to the limited availability of flexible demand. Given the significant variation and the fact that the surplus was not eliminated in any month, the value of flexible demand under the conditions of the case study may be limited. The key practical takeaway from this paper is the methodology for representing the availability of flexible demand from residential heat pumps, which is applicable to country-level EnergyPLAN models.